Treatment of Recurrent Focal Segmental Glomerulosclerosis in Pediatric Kidney Transplant Recipients: Effect of Rituximab - Christine Sethna; Corinne Benchimol; Hilary Hotchkiss; Rachel Frank; Lulette Infante; Suzanne Vento; Howard Trachtman (Journal of Transplantation)
Recurrence of focal segmental glomerulosclerosis (FSGS) after renal transplantation is a complication that often leads to graft loss. There is no consensus on the optimal treatment of recurrent FSGS. Rituximab, a monoclonal antibody to CD20, may be a useful treatment of this complication. Methods. We report four pediatric cases of recurrent FSGS treated with rituximab and plasmapheresis. Results. Four children (2M/2F), age 15.3 ± 2.6, with recurrent FSGS posttransplant were identified. Four doses of rituximab were administered 171 ± 180 days posttransplant and 114 ± 169 days after the start of plasmapheresis. Three children responded with complete remission, one of whom relapsed after four months. One child had a partial response with a decrease in proteinuria that was not sustained. No adverse side effects were reported during treatment or followup (mean 22.5 months). Conclusions. Rituximab is a safe and well-tolerated ancillary treatment for recurrent FSGS in pediatric patients in conjunction with plasmapheresis.